External assurance on sustainability report disclosure and firm value: evidence from Indonesia and Malaysia - Iman Harymawan, - (Entrepreneurship And Sustainability Center, 2020)
We analyze the content of assurance statements on sustainability reports to examine the extent of external assurance on sustainability report disclosure in Indonesian and Malaysian listed companies and identify their impact on firm value. This research is conducted using 84 samples of listed companies from all industries, except the financial industry, for the period 2010-2016. Ordinary least square (OLS) regression is used to test the research hypothesis. The results show a significant positive effect of external assurance on sustainability report disclosure to a firm value measured by Tobins’Q. Besides, we also found that companies in Indonesia have higher disclosure in terms of external assurance for sustainability reports compared to Malaysia. This study adds new evidence to the literature on sustainability assurance in emerging countries.